Heterophoria analysis of HIV/AIDS patients on highly active antiretroviral therapy in Northwestern Nigeria - Ifeanyichukwu, Philips E.; Habib, Saudat G.; Udo, Ubani; Hassan, Sadiq; Hypolytus, Muoneke C.; Sunusi, Shemau; Sani, Rabi Y.; Chidinma, Ezeigbo Amarachi; O. Elemba, Jacqueline; Ibrahim, Usman Y.; Lawan, Abdu (International Journal of Research in Medical Sciences, 2025)
Background: Despite the efficacy of highly active antiretroviral therapy (HAART) on HIV, there are other ocular side effects of HAART which are yet to be determined and characterized. The aim of the study was to determine and characterize the pattern of latent deviation of eyes among HIV/AIDS patients. Methods: Consenting patients were recruited and grouped into two groups A and B. Group A were HAART naive, while group B were HAART experienced. These were further subdivided into four groups; comprising of B1: on HAART from 0>2½ years, B2: 2½>5 years, B3: 5>7½ years, and B4: 7½ >10 years. Results: There were 400 participants aged 25-55 years with a mean age of 37.86±7.5 years. About 135 (33.8%) and 129 (32.3%) were Orthophoric for habitual phoria at near and far (HPN and HPF), while 207 (51.7%) and 218 (54.5%) were also Orthophoric for induced phoria at far and near (IPN and IPF) respectively. There was a statistically significant association between effect and HAART duration with induced lateral phorias at both distances (p=0.01), no association with CD4+ T-cells count, HAART Regimen and habitual lateral phorias at both distances (p=0.06 and p=0.95). Conclusions: HIV/AIDS patients on HAART exhibit either convergence excess or divergence insufficiency as a binocular vision syndrome depending on the degree of deviation both at far and near distances. The effect and duration of HAART are statistically significant with induced lateral phorias at both distances (p=0.01).